Identification of sex pheromones of clearwing moths Synanthedon cephiformis (Ochsenheimer, 1808), S. loranthi (Králíček, 1966) and S. spuleri (Fuchs, 1908) (Lepidoptera: Sesiidae) in Slovenia - Predovnik, Željko (Acta entomologica slovenica (Ljubljana), 2014)
The results are presented of faunistic research of the morphologically similar and related clearwing moth species Synanthedon cephiformis (Ochsenheimer, 1808), S. loranthi (Králíček, 1966) and S. spuleri (Fuchs, 1908) in Slovenia using the method of pheromone traps. New sex attractants for males of the species S. cephiformis and S. loranthi were discovered, which are also the first known effective pheromones for S. cephiformis in general. The distribution and biology of the mentioned species in Slovenia are briefly described. External morphological characters for the determination of males caught in pheromone traps of species of the S. tipuliformis group are given, as well as the composition of the effective pheromones and a phylogenetic tree.
Keywords: feromoni; Lepidoptera; metulji; pheromones; Sesiidae; Slovenia; Slovenija; Synanthedon